Roles of Community Pharmacists in Cancer Management - Oluwaseyi Muyiwa Egbewande; Muhsinah Adesewa Abdulwasiu; Rashidat Onyinoyi Yusuf; Aishat Bisoye Durojaye; Zainab Ikeoluwa Ashimiyu-Abdusalam (University of Minnesota Libraries Publishing, 2022)
Community pharmacists are among the most easily accessible healthcare practitioners and are usually the first point of contact with the public or community. This is often due to their accessibility, credibility, and widespread within the public sector making them essential members of the healthcare team with significant contributions to the delivery of public health care. Community pharmacists, in addition to their known educational and awareness-raising roles, may play an essential role in risk assessment and screening of patients, detection of symptoms of probable malignancy, and cancer treatments. The pharmacy profession has been evolving from dispensing roles into more patient-oriented outcomes and pharmacists are now participating in more clinical interventions. This places community pharmacists in the best position to provide the necessary knowledge and healthcare to benefit populations at risk of cancer.  Active involvement of community pharmacists in the care and management of cancer will significantly contribute to screening and risk assessment, early detection, treatment and eradication of breast, cervical, lung, ovarian and other forms of cancer. As a result, the community pharmacy setting must the developed to maximize its full potential in cancer care.